A literature review: The relationship between welding fume exposure and welders' lung function disorders: toxicological study - Isnin Aulia Ulfah Mu’awanah; Siti Nurkhasanah; Arif Yusuf Wicaksana (Universitas Jenderal Achmad Yani Yogyakarta, 2021)
Background: Welding is the process of combining two types of metal or other material particles into one by melting and cooling processes. Welding fumes and welding metal fumes have a risk of lung function disorders in welding workers.Objective: This study aimed to discover the relationship between the effect of exposure to welding smoke and pulmonary function disorders in welding workshop workers based on the years of service and the use of PPE (masks).Methods: This research was a literature review using secondary data sources through the Google Scholar and Pubmed databases published in 2010-2020.Results: Vital lung capacity of ≥ 5 years welders have a higher risk of having lung function disorders. Welders who use PPE (masks) as many as 48 workers (21%) and 179 workers (79%) do not use PPE (masks) during the work. Welders who do not consistently wear masks are twice as likely to have lung function disorders. Conclusion: Welders having years of service ≥ 5 years are more at risk of experiencing lung function disorders than years of service < 5 years. The mask usage affects the welders’ lung function health.